2021
DOI: 10.1093/plcell/koaa054
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific phospholipase C4 hydrolyzes phosphosphingolipids and sustains plant root growth during phosphate deficiency

Abstract: Phosphate is a vital macronutrient for plant growth, and its availability in soil is critical for agricultural sustainability and productivity. A substantial amount of cellular phosphate is used to synthesize phospholipids for cell membranes. Here, we identify a key enzyme, nonspecific phospholipase C4 (NPC4) that is involved in phosphosphingolipid hydrolysis and remodeling in Arabidopsis during phosphate starvation. The level of glycosylinositolphosphorylceramide (GIPC), the most abundant sphingolipid in Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…2008; Nakamura et al, 2005;Wimalasekera et al, 2010;Yang et al, 2021). In summary, a model for the regulation of subcellular localization of NPC4 and NPC5 in plants was proposed (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2008; Nakamura et al, 2005;Wimalasekera et al, 2010;Yang et al, 2021). In summary, a model for the regulation of subcellular localization of NPC4 and NPC5 in plants was proposed (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…However, the loss of NPC4 had no overt effect on decreasing PC in leaves (Nakamura et al, 2005) or in roots, except at an early stage (Su et al, 2018) during phosphate deficiency, indicating that PC may not be the major substrate of NPC4 during this stress condition. Recently, we have found that NPC4 hydrolyzes GIPC and that a loss of NPC4 in Arabidopsis impeded the decrease in GIPC induced by phosphate deficiency (Yang et al, 2021). Here, we show that introducing the non‐acylating NPC4 C533A into npc4‐1 fails to functionally restore the level of GIPC to that found in the WT, but that introducing the WT NPC4 does restore GIPC to WT level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that a GIPC phospholipase C activity which cleaves phospholipids before the phosphate group, is specifically promoted in that condition. It is worth to note that the non-specific phospholipase C4 (NPC4) has been shown to be involved in GIPC hydrolysis in response to phosphate deficiency 20 and consequently, IPGs could act more broadly as stress-related molecules. The accumulation of serie A IG (m/z 517) also suggests that a GIPC phospholipase D, which cleaves after the phosphate moiety, could be activated.…”
Section: Introductionmentioning
confidence: 99%